Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
1. 2x+2-(2x-14)=5x+2
0x+16=5x+2
16=5x+2
14=5x
14/5=x or 2.8=x
2. 2x+10-(-2x+7)=-7x+14
4x+3=-7x+14
11x+3=14
11x=11
x=1
Step-by-step explanation:
Hope this helps
1) x=2.8
2) x=1
Step-By-Step:
Q1) 2x + 2 - (2x - 14) = 5x + 2
Simply the expression
2x+2-2x+14=5x+2
collect like terms
(2x-2x) + (2+14) = 5x+2
simplify
16= 5x+2
swap sides
5x+2=16
-2 -2
5x=16-2
5x=14
to get x on its own we divide each side by 5 so
5x=14
÷5 ÷5
x= 2.8
Q2) 2x + 10 - (-2x + 7) = -7x + 14
Simply the expression
2x+10+2x-7= -7+14
collect like terms
(2x+2x)+(10-7)= -7+14
simplify
4x+3=7
-3 -3
4x+3-3=7-3
simplify
4x=7-3
4x=4
to get x on its own divide each side by 4 so...
4x=4
÷4 ÷4
x=1
Hope this helped- have a good day bro cya)
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.